2022
DOI: 10.3389/fimmu.2022.1039427
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chronic immune response and neurodegenerative damage in long COVID-19

Abstract: In the past two years, the world has faced the pandemic caused by the severe acute respiratory syndrome 2 coronavirus (SARS-CoV-2), which by August of 2022 has infected around 619 million people and caused the death of 6.55 million individuals globally. Although SARS-CoV-2 mainly affects the respiratory tract level, there are several reports, indicating that other organs such as the heart, kidney, pancreas, and brain can also be damaged. A characteristic observed in blood serum samples of patients suffering CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 181 publications
1
17
0
Order By: Relevance
“…As we have already discussed in this review article, long COVID could be induced by different mechanisms, including viral persistence that leads to chronic activation of the immune system and reactivation of latent viruses, the release of superantigens that over-activate the immune system, alteration in the gut microbiota, and damage to the gut and blood–brain barriers which collectively may result in autoimmunity and polyautoimmunity, including neuroautoimmunity [ 43 , 44 , 93 , 95 , 213 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we have already discussed in this review article, long COVID could be induced by different mechanisms, including viral persistence that leads to chronic activation of the immune system and reactivation of latent viruses, the release of superantigens that over-activate the immune system, alteration in the gut microbiota, and damage to the gut and blood–brain barriers which collectively may result in autoimmunity and polyautoimmunity, including neuroautoimmunity [ 43 , 44 , 93 , 95 , 213 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neuroinflammatory basis of brain fog in COVID survivors has been compared to that of cancer-therapy induced cognitive impairment, with white matter microglial reactivity and consequent neural dysregulation (Fernández-Castañeda et al ., 2022). Chronic cytokinemia affecting BBB permeability, inducing neurotoxicity, plus the generation of autoantibodies resulting in the interference with neurogenesis, neuronal repair, chemotaxis and microglia function naturally would result in cognitive impairment (Elizalde-Díaz et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…67 Chronic cytokinemia and inflammation can alter BBB permeability and induce neurotoxicity, and autoantibodies generated can alter neurogenesis, neuronal repair, and the function of microglia. 68 Meanwhile, others showed that the spike protein could damage the endothelium and BBB, which leads to perivascular inflammation. 69 However, a large cohort study reported that the vaccination with the mRNA COVID-19 vaccine was not associated with thrombotic events, hemorrhage, thrombocytopenia, or brain injury.…”
Section: Brain Infection and Blood-brain Barrier Damagementioning
confidence: 99%